2018
DOI: 10.1177/1747021818762669
|View full text |Cite
|
Sign up to set email alerts
|

Paired associate learning deficits in poor readers: The contribution of phonological input and output processes

Abstract: It is well-established that poor readers exhibit deficits in paired associate learning (PAL), and there is increasing evidence for a phonological locus of these deficits. However, it remains unclear whether poor performance stems from difficulties specific to the phonological output system or difficulties that affect both phonological input and output processes. Understanding these deficits is important not only in the context of PAL but also for informing broader theories of typical and atypical reading devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 75 publications
(134 reference statements)
1
15
0
Order By: Relevance
“…Although we cannot adjudicate amongst these possible explanations based on the data we collected, the current study nonetheless adds to a growing literature documenting word learning deficits in children with RD and/or DLD compared to TD children (Alt et al., 2017, 2019; James et al., 2019; Kan & Windsor, 2010; Kimppa et al., 2018; Landi et al., 2018; Litt et al., 2019). Furthermore, the current findings help clarify the contexts in which potential word learning deficits are apparent.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Although we cannot adjudicate amongst these possible explanations based on the data we collected, the current study nonetheless adds to a growing literature documenting word learning deficits in children with RD and/or DLD compared to TD children (Alt et al., 2017, 2019; James et al., 2019; Kan & Windsor, 2010; Kimppa et al., 2018; Landi et al., 2018; Litt et al., 2019). Furthermore, the current findings help clarify the contexts in which potential word learning deficits are apparent.…”
Section: Discussionmentioning
confidence: 71%
“…(2017), who observed that children with RD were comparable to TD children on the PAL aspects of a word learning task, but struggled when asked to assess the phonology of a newly learned word. Furthermore, Litt, Wang, Sailah, Badcock, and Castles (2019) found that children with RD were impaired on visual‐to‐verbal learning (requiring input and output phonology) but not verbal‐to‐visual learning (requiring only input phonology); see also Litt and Nation (2014) for similar findings. This pattern of findings suggests that children with RD may only be impaired in PAL for tasks that have a phonological output demand.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is also theoretically relevant whether PAL training performance is correlated with reading ability, given that previous studies have studied PAL in relation to developmental dyslexia ( Hulme, Goetz, Gooch, Adams, & Snowling, 2007 ; Litt, de Jong, van Bergen, & Nation, 2013 ; Litt & Nation, 2014 ; Litt, Wang, Sailah, Badcock, & Castles, 2018 ). This appears to be the case from the subset data in Table 1 , but not from the analyses including all participants who passed the PAL training task.…”
Section: Resultsmentioning
confidence: 99%
“…In research settings, memory interference is often measured using a paired-associative task-tasks that include pairs of objects (e.g., pictures, words), which are to be memorized and subsequently recalled [59][60][61]. For this experiment, the AB-DE AC-FG paired-associative paradigm was utilized.…”
Section: Memorymentioning
confidence: 99%